The Essence of Education and Character Education in the Paradigm of Critical Education Philosophy - I Wayan Agus Gunada (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2023)
The writing of this study is to explain education and character education from the point of view of critical educational philosophy. Education is a process to achieve competence and self-maturation, and character education is currently essential in overcoming moral degradation. However, its implementation still needs to be strengthened, considering that there are still many phenomena of juvenile delinquency in school-age children. So that studies in the critical paradigm are essential to be carried out to put back the position of education and the implementation of character education in the learning process in educational institutions. This study uses qualitative research with a literature study approach; analysis uses a reduction analysis model, data presentation, and verification. The results of the interpretation can be explained that the study of critical philosophy in education seeks to criticize the essence of education and character education that is understood today. Proper education is not only the process that runs in schools, but education runs within the family, school, and community. Character education is a process of internalization, and integration of values, in order to realize students with character and become a guideline for attitudes and behavior, as well as moral awareness to mitigate moral degradation by students, so it must be strengthened not only in the policy context but must be strengthened in its implementation. This study can increase knowledge about the philosophy of critical education and is helpful to be a reference library for relevant studies.